2021
DOI: 10.1002/star.202100077
|View full text |Cite
|
Sign up to set email alerts
|

Pickering Emulsions Stabilized by Cyclodextrin Nanoparticles: A Review

Abstract: Pickering emulsions, stabilized by solid particles at the oil/water interface, are brought into focus due to their long‐term stability additional functionality and higher safety. Cyclodextrins are enzymatic derivatives of starch which have a hydrophobic inside cavity and a hydrophilic outside surface. Cyclodextrins aggregate and form crystalline nanoparticles at the interface of oil/water by self‐assembly which adsorbs on the surface of oil droplets to maintain the long‐term stability of the emulsion during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 71 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…Studies comparing α-CD, β-CD, and γ-CD have revealed that β-CD exhibits the most pronounced emulsifying effect in the formation of Pickering emulsions [35,36].…”
Section: Emulsions Formation Stability and Active Compounds Concentra...mentioning
confidence: 99%
“…Studies comparing α-CD, β-CD, and γ-CD have revealed that β-CD exhibits the most pronounced emulsifying effect in the formation of Pickering emulsions [35,36].…”
Section: Emulsions Formation Stability and Active Compounds Concentra...mentioning
confidence: 99%
“…In food and pharmaceutical fields, the commonly used Pickering particles mainly include protein (zein, soy protein, and other protein particles), polysaccharides (starch, chitosan, celluloses, and other polysaccharide particles), cyclodextrins (CDs) and their derivatives, and other small particles. In other fields such as the daily chemical industry, leather industry, home textile industry, ecological environment field, and inorganic particles such as titanium dioxide particles, silica particles, and carbon nanotubes are commonly used as Pickering particles ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In other fields such as the daily chemical industry, leather industry, home textile industry, ecological environment field, and inorganic particles such as titanium dioxide particles, silica particles, and carbon nanotubes are commonly used as Pickering particles (4). Cyclodextrins (CDs) are a kind of cyclic oligosaccharides with cyclic glucose as the basic structural unit, which is produced by the degradation of starch by cycloglycosyltransferases produced by various bacilli (5).…”
mentioning
confidence: 99%
“…19 Magnetic Fe 3 O 4 nanoparticles possess the dual advantages of nanoscale and magnetic particles. In addition, the modification of Fe 3 O 4 nanoparticles by organic polymers, such as cellulose, [20][21][22][23] cyclodextrins, 24,25 chitosan (CS), [26][27][28][29][30] as well as other polymers, [31][32][33] has been reported. The polymer in this composite material can effectively inhibit the agglomeration of magnetic nanoparticles, increase the surface effect of magnetic nanoparticles, and also introduce specific active functional groups on the polymer into the magnetic material.…”
Section: Introductionmentioning
confidence: 99%